An isoindoline bridged [M(η6-arene)2]+ (M = Re, 99mTc) ansa-arenophane and its dinuclear macrocycles with axial chirality. Issue 25 (13th June 2022) - Csucker, Joshua; Jo, Da Kyung; Nadeem, Qaisar; Blacque, Olivier; Fox, Thomas; Braband, Henrik; Alberto, Roger
Abstract : We report the synthesis of novel rhenium and 99m Tc ansa -arenophane complexes with bridging isoindolines. Inter-instead of intramolecular isoindoline formation leads to dinuclear macrocycles, one of which exhibits axial chirality. Abstract : This work presents a straightforward method for the preparation of an isoindoline bridged [M(arene)2 ] + (M = Re, 99m Tc) ansa -[3]arenophane. This intramolecular formation of an ansa -complex is accompanied by the intermolecular formation of a pair of isoindoline bridged macrocyclic dinuclear sandwich complexes, one of which exhibits axial chirality.